Avaliação genética de bovinos da raça Nelore em diferentes condições de criação - Viana, Alexandra Fabielle Pereira (2019)
The objective of this study was to estimate genetic parameters for the productive, reproductive and morphological characteristics of Nellore animals, to verify how the breeding values of the traits are distributed in different Brazilian states and to suggest a selection index by state/sex. The genetic parameters were estimated by uncharacteristic analysis under animal model, using the MLRM method. Estimate genetic values (EBV) of higher heritability characteristics and age at first calving were explored by principal component analysis. Participating males of performance test and grass-fed showed better EBVD400, EBVP550 and EBVPE550, however, the test participants in stable had the best VGs for the visual scores. For females the best EBVD400 were from the animals in stable, regardless of the age of weaning. In state of PR they are the best EBVP550 and EBVD400 in males and females, however, in MG the best EBVs for the reproductive characteristics of males and females. Principal component analysis assists in determining the characteristics that explain most of the data variation and also through the principal component 1 is a good alternative in the elaboration of selection index that can be defined considering the environmental differences.